Carbon Nitride/Reduced Graphene Oxide Film with Enhanced Electron Diffusion Length: An Efficient Photo‐Electrochemical Cell for Hydrogen Generation. Issue 23 (28th May 2018) - Peng, Guiming; Volokh, Michael; Tzadikov, Jonathan; Sun, Jingwen; Shalom, Menny
Abstract: Polymeric carbon nitride (CN) has emerged as a promising semiconductor for energy‐related applications. However, its utilization in photo‐electrochemical cells is still very limited owing to poor electron–hole separation efficiency, short electron diffusion length, and low absorption coefficient. Here the synthesis of a highly porous carbon nitride/reduced graphene oxide (CN‐rGO) film with good photo‐electrochemical properties is reported. The CN‐rGO film exhibits long electron diffusion length and high electrochemical active surface area, good charge separation, and enhanced light‐harvesting properties. The film displays a 20‐fold enhancement of photocurrent density over pristine CN, reaching up to 75 µA cm −2 at 1.23 V versus reversible hydrogen electrode (RHE) in an alkaline solution, as well as stability over a wide pH range. Photocurrent measurements with a hole scavenger reveal a photocurrent density of 660 µA cm −2 at 1.23 V versus RHE and a quantum efficiency of 60% at 400 nm, resulting in the production of 0.8 mol h −1 g −1 of hydrogen. The substantial photo‐electrochemical activity enhancement and hydrogen production together with the low price, high electrochemical surface area, long electron diffusion length, stability under harsh condition, and tunable photophysical properties of CN materials open many possibilities for their utilization in (photo)electrochemical and electronic devices. Abstract : A simple and straightforward synthesis of highly porous carbon nitride layer/reduced graphene oxide films with long electron diffusion, high electrochemical surface area, and good charge separation properties is shown. Photo‐electrochemical measurements reveal high photocurrent densities, good stability in alkaline and acidic solution, and high quantum efficiencies, resulting in the sustainable production of hydrogen.